Characterization of Grape Molasses/Sesame Paste/Honey Blends: Multiple Response Optimization of Some Physicochemical, Bioactive, Viscoelastic and Sensory Properties - Karaman, Safa; Yilmaz, Mustafa Tahsin; Ozturk, Gokturk; Yuksel, Ferhat; Toker, Omer Said; Dogan, Mahmut (WILEY, 2017)
In this study, blends of grape molasses, sesame paste and honey were prepared at different ratios according to the mixture design and some physicochemical, rheological, bioactive and sensory properties of final blends were studied to create the optimum formulation for the final product. The results showed that the mixture components had significant change on the studied parameters (P 0.71) were constructed for the studied parameters. Multiple response optimization results showed that the most preferred blend should contain 34.66% of grape molasses, 34.11% of sesame paste and 31.23% of honey. Practical ApplicationsGrape molasses, honey and sesame paste are commonly consumed food products which are rich in energy and many functional components. The people generally consume them in their daily diets especially in their breakfasts. To combine their functionality and sensory properties, an optimization procedure was applied and the mostly desired blend was determined. Blending affected the rheological, textural and bioactive properties of the sample significantly. The results of the study are very important for food industry.
Keywords: RHEOLOGICAL CHARACTERISTICS; TEMPERATURE; BEHAVIOR; STEADY; Engineering; Food Science & Technology